The Causes of Long Waiting Times for Outpatient Pharmaceutical Prescription Services at Hospital “X” in Padang - Astiena, Adila Kasni; Khairunnisa, Mutia; Kasra, Kamal; Azmi, Fadilla (JSFK (Jurnal Sains Farmasi & Klinis), 2022)
Outpatient pharmacy services in a hospital shows the quality of health service to the community. Data from the internal quality assurance report of Hospital â€Xâ€ in Padang showed that only 93.76% of non-compounded medication and 94.6% of compounded medication recipes met the waiting time standard. This study aimed to analyze the causes of the long waiting time for outpatient pharmacy services at Hospital â€œXâ€. The type of this research was a mix-method sequential type explanatory, conducted from February until May 2022. The quantitative design was a cross-sectional study of 141 for non-concoction and 35 for compounded medication recipes determined by quota sampling. Qualitative research was conducted on seven informants by purposive sampling. Observation, in-depth interviews, and document review collected data. Results showed that the average waiting time was 84.19 (standard â‰¤30) minutes for non-concoction and 164.58 (standard â‰¤60) minutes for compounded medication recipes. The causes of the long waiting time were a need for more staff, prescriptions outside the hospital formulary, equipment errors, and medicines delivery delays. There should be a job redesign by rearranging the shift picket for pharmacy staff, regular equipment maintenance, and updating standard operating procedures related to medicines delivery to the patients.